Efficient Bi-Iterative Method for Source Position and Propagation Speed Estimation Using TDOA Measurements - Guo-Hui Zhu; Da-Zheng Feng; Yan Zhou (International Journal of Distributed Sensor Networks)
This paper develops an efficient bi-iterative source location and propagation speed estimation method utilizing time difference of arrival (TDOA) measurements. The source location and propagation speed estimation is a nonlinear problem due to the nonlinearity in the TDOA measurement equations. The newly developed bi-iterative method computes the source location and propagation speed alternately. The asymptotic convergence of the new bi-iterative method is theoretically analyzed. First-order perturbation analysis is applied to the newly developed solution to derive its bias and variance. The first-order analytical results show that the proposed method provides approximately unbiased source position and propagation speed estimates for low noise levels and the accuracy of these estimates approaches the Cramer-Rao lower bound (CRLB). The extension of the new bi-iterative method to the more general situation where the sensor locations are subject to random errors is also presented. Simulation studies are given to show the good performance of the proposed method.